Between ants, humans, disciplinarities and worldviews: creating a performative work from an interdisciplinary starting-point - Fentz, Christine (Peripeti, 2021)
This article examines the interdisciplinary working processes involved in creating a performing arts piece about ants. It maps the collaboration between performing artists and scientists from other research areas. It is an investigation of how to approach interdisciplinary work while also navigating different worldviews, using each other as new prisms on oneself and on unknown material.